2009
DOI: 10.4196/kjpp.2009.13.4.327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan on Catecholamine Release in the Isolated Rat Adrenal Gland

Abstract: The aim of this study was to determine whether losartan, an angiotensin II (Ang II) type 1 (AT1) receptor could influence the CA release from the isolated perfused model of the rat adrenal medulla. Losartan (5∼ 50 μM) perfused into an adrenal vein for 90 min produced dose-and time-dependent inhibition of the CA secretory responses evoked by ACh (5.32 mM), high K + (56 mM, a direct membrane depolarizer), DMPP (100 μM) and McN-A-343 (100 μM). Losartan failed to affect basal CA output. Furthermore, in adrenal gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…It can be suggested that a specific losartan mechanism of action is involved in the enhancement of the anticonvulsant activity of LTG. It has been reported that losartan inhibits voltage‐dependent Na + channels in the rat adrenal medulla as in the presence of losartan, veratridine‐evoked (an activator of Na + channels) catecholamine secretion was greatly inhibited . On the other hand, telmisartan delays the inactivation of voltage‐gated Na + channels in cardiomyocytes .…”
Section: Discussionmentioning
confidence: 99%
“…It can be suggested that a specific losartan mechanism of action is involved in the enhancement of the anticonvulsant activity of LTG. It has been reported that losartan inhibits voltage‐dependent Na + channels in the rat adrenal medulla as in the presence of losartan, veratridine‐evoked (an activator of Na + channels) catecholamine secretion was greatly inhibited . On the other hand, telmisartan delays the inactivation of voltage‐gated Na + channels in cardiomyocytes .…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that chronic blockade of RAAS may decrease the excess sypatheic responses to stress in cardiovascular diseases and prevent the likely development of Type II diabetes mellitus [11]. Previously, we found that losartan inhibits significantly the CA secretion evoked by Ang II in the perfused rat adrenal medulla [12]. Armando and his colleagues [47] also found that pre-treatment with candesartan, an ARB, eliminated the increase in adrenal NE and EP concentrations induced by isolation stress.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that other ARBs, such as losartan and olmesartan also inhibit the CA secretion from the perfused rat adrenal gland, which is mediaited through blockade of AT 1 recptors [12,13]. In spontaneously hypertensive rats (SHRs), oral administration of AT 1 antagonist (candesartan) can effectively block central actions of Ang II, regulating blood pressure and reaction to stress, and selectively and differentially modulating sympathoadrenal responses [14].…”
Section: Introductionmentioning
confidence: 99%